Cytokine accumulation in osteitis fibrosa of renal osteodystrophy - Duarte,M.E.L. (2002)
Bone marrow fibrosis occurs in association with a number of pathological states. Despite the extensive fibrosis that sometimes characterizes renal osteodystrophy, little is known about the factors that contribute to marrow accumulation of fibrous tissue. Because circulating cytokines are elevated in uremia, possibly in response to elevated parathyroid hormone levels, we have examined bone biopsies from 21 patients with end-stage renal disease and secondary hyperparathyroidism. Bone sections were stained with antibodies to human interleukin-1alpha (IL-1alpha), IL-6, IL-11, tumor necrosis factor-alpha (TNF-alpha) and transforming growth factor-ß (TGF-ß) using an undecalcified plastic embedding method. Intense staining for IL-1alpha, IL-6, TNF-alpha and TGF-ß was evident within the fibrotic tissue of the bone marrow while minimal IL-11 was detected. The extent of cytokine deposition corresponded to the severity of fibrosis, suggesting their possible involvement in the local regulation of the fibrotic response. Because immunoreactive TGF-ß and IL-6 were also detected in osteoblasts and osteocytes, we conclude that selective cytokine accumulation may have a role in modulating bone and marrow cell function in parathyroid-mediated uremic bone disease.